The New British Colonialism: British Policy of Influence in the Arab Gulf States after the Withdrawal (1971-1991) - BÖLME, SELİN MUZAFFER (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2020)
This paper aims to analyze Britain's relations with the former colonies in the Gulf after the termination of the British protectorate in the Persian Gulf and discuss how the British colonial ties influenced the post-colonial relations with the Arab Gulf States. Archive documents, official papers and secondary sources were used in order to determine and compare the relations in pre/post withdrawal periods and the results were analyzed in frame of the Post-colonial theory. The main argument of this study is that the British colonial relations and ties, which had been constructed in political, military, economic and institutional spheres in the colonial era, were significant determinants in reshaping the new British foreign policy towards the Arab Gulf States. Britain, who successfully adopted the colonial relations in the new term, managed to preserve its interests after the withdrawal and even extended some of them in certain fields such as the oil sector.
Keywords: Britain; British Foreign Policy; Persian Gulf; Colonialism; Post-Colonialism